CBSE Class 7 Maths – MCQ and Online Tests – Unit 4 – Simple Equations
Every year CBSE students attend Annual Assessment exams for 6,7,8,9,11th standards. These exams are very competitive to all the students. So our website provides online tests for all the 6,7,8,9,11th standards’ subjects. These tests are also very effective and useful for those who preparing for any competitive exams like Olympiad etc. It can boost their preparation level and confidence level by attempting these chapter wise online tests.
These online tests are based on latest CBSE syllabus. While attempting these, our students can identify their weak lessons and continuously practice those lessons for attaining high marks. It also helps to revise the NCERT textbooks thoroughly
CBSE Class 7 Maths – MCQ and Online Tests – Unit 4 – Simple Equations
Question 1.
The solution of the equation 5p + 2 = 7 is
(a) 0
(b) 1
(c) -1
(d) 2
Answer
Answer: (b) 1
Hint:
5p + 2 = 71 ? 5p = 7 – 2 = 5
? p = \(\frac{5}{5}\) = 1.
Question 2.
The solution of the equation 3p – 2 = 4 is
(a) 0
(b) 1
(c) 2
(d) 3
Answer
Answer: (c) 2
Hint:
3p – 2 = 4 ? 3p = 4 + 2 = 6
? P = \(\frac{6}{3}\) = 2
Question 3.
Write the following statement in the form of an equation:
One fourth of n is 3 more than 2
(a) \(\frac { n }{ 4 } \) – 2 = 3
(b) \(\frac { n }{ 4 } \) + 2 = 3
(c) \(\frac { n }{ 2 } \) – 4 = 3
(d) \(\frac { n }{ 2 } \) + 4 = 3
Answer
Answer: (a) \(\frac { n }{ 4 } \) – 2 = 3
Question 4.
Write the following statement in the form of an equation:
One third of a number plus 2 is 3
(a) \(\frac { m }{ 3 } \) – 2 = 3
(b) \(\frac { m }{ 3 } \) + 2 = 3
(c) \(\frac { m }{ 2 } \) – 3 = 3
(d) \(\frac { m }{ 2 } \) + 3 = 3
Answer
Answer: (b) \(\frac { m }{ 3 } \) + 2 = 3
Question 5.
Write the following statement in the form of an equation:
Taking away 5 from x gives 10
(a) x – 5 = 10
(b) x + 5 = 10
(c) x – 10 – 5
(d) none of these
Answer
Answer: (a) x – 5 = 10
Question 6.
Write the following statement in the form of an equation:
Four times a number p is 8.
(a) 4P = 8
(b) P + 4 = 8
(c) p – 4 = 8
(d) p ÷ 4 = 8
Answer
Answer: (a) 4P = 8
Question 7.
Write the following statement in the form of an equation:
Add 1 to three times n to get 7
(a) 3n + 1 = 7
(b) 3n – 1 = 7
(c) 3n + 7 = 1
(d) none of these
Answer
Answer: (a) 3n + 1 = 7
Question 8.
Write the following statement in the form of an equation:
The sum of three times x and 10 is 13.
(a) 3x + 10 = 13
(b) 3x – 10 = 13
(c) 3x + 13 = 10
(d) none of these
Answer
Answer: (a) 3x + 10 = 13
Question 9.
Write the following statement in the form of an equation:
If you subtract 3 from 6 times a number, you get 9
(a) 3x – 6 = 9
(b) 6x – 3 = 9
(c) 6x + 3 = 9
(d) 3x + 6 = 9
Answer
Answer: (b) 6x – 3 = 9
Question 10.
The solution of the equation x – 6 = 1 is
(a) 1
(b) 6
(c) -7
(b) 7
Answer
Answer: (d) 7
Hint:
x – 6 = 1 ? x = 1 + 6 = 7.
Question 11.
The solution of the equation 5x = 10 is
(a) 1
(b) 2
(c) 5
(d) 10
Answer
Answer: (b) 2
Hint:
5x = 10 ? x = \(\frac{10}{5}\) = 2
Question 12.
The solution of the equation 4p – 3 = 9 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (c) 3
Hint:
4p – 3 = 9 ? 4p = 9 + 3 = 12
? p = \(\frac{12}{4}\) = 3.
Question 13.
Write the following statement in the form of an equation:
The number b divided by 6 gives 5.
(a) \(\frac { b }{ 6 } \) = 5
(b) b – 5 = 6
(c) 5b = 6
(d) b + 5 = 6
Answer
Answer: (a) \(\frac { b }{ 6 } \) = 5
Question 14.
The solution of the equation x + 3 = 0 is
(a) 3
(b) -3
(c) 0
(d) 1
Answer
Answer: (b) -3
Hint:
x + 3 = 0 ? x = -3.
Question 15.
The solution of the equation p + 4 = 4 is
(a) 0
(b) 4
(c) -4
(d) 8
Answer
Answer: (a) 0
Hint:
p + 4 = 4 ? P = 4 – 4 = 0.
Question 16.
The solution of the equation m – 1 = 2 is
(a) 1
(b) 2
(c) 3
(d) 6
Answer
Answer: (c) 3
Hint:
m – 1 = 2 ? m = 2 + 1 = 3.
Question 17.
The solution of the equation 2m = 4 is
(a) 1
(b) 2
(c) -1
(d) -2
Answer
Answer: (b) 2
Hint:
2m = 4 ? m = \(\frac{4}{2}\) = 2
Question 18.
The solution of the equation \(\frac { m }{ 3 } \) = 3 is
(a) 3
(b) 6
(c) 9
(d) 12
Answer
Answer: (c) 9
Hint:
\(\frac{m}{3}\) = 3 ? m = 3 × 3 = 9.
Question 19.
The solution of the equation = 6 is
(a) 6
(b) 7
(c) 14
(d) 3
Answer
Answer: (c) 14
Hint:
\(\frac{3m}{7}\) = 6 ? 3m = 7 × 6 = 42
? m = \(\frac{42}{3}\) = 14
Question 20.
The solution of the equation 3p + 5 = 8 is
(a) -1
(b) 1
(c) 3
(d) 5
Answer
Answer: (b) 1
Hint:
3p + 5 = 8 ? 3p = 8 – 5 = 3
? P = \(\frac{3}{3}\) = 1 4p – 2 = 10
Question 21.
The solution of the equation 4p – 2 = 10 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (c) 3
Hint:
4p – 2 = 10 ? 4p = 10 + 2 = 12
? p = \(\frac{12}{4}\) = 3.
Question 22.
The solution of the equation 2p – 1 = 3 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (b) 2
Hint:
2p – 1 = 3 ? 2p = 3 + 1 = 4
? p = \(\frac{4}{2}\) = 2.
Question 23.
The solution of the equation \(\frac { m }{ 2 } \) = 3 is
(a) 2
(b) 3
(c) 12
(d) 6
Answer
Answer: (d) 6
Hint:
\(\frac{m}{2}\) = 3 ? m = 3 × 2 = 6.
Question 24.
The solution of the equation 7n + 5 = 12 is
(a) 0
(b) – 1
(c) 1
(d) 5
Answer
Answer: (c) 1
Hint:
7n + 5 = 12 ? 7n = 12 – 5
? 7n = 1 ? n = \(\frac{7}{7}\) = 1.
Question 25.
The solution of the equation y – 4 = – 1 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (c) 3
Hint:
y – 4 = -1 ? y = 4 – 1 = 3.
Question 26.
The solution of the equation y + 2 = -2 is
(a) 2
(b) -2
(c) 4
(d) -4
Answer
Answer: (d) -4
Hint:
y + 2 = -2 ? y = -2 – 2 = -4.
Question 27.
The solution of the equation 10t = -20 is
(a) 1
(b) -1
(c) 2
(d) -2
Answer
Answer: (d) -2
Hint:
10t = -20 ? t = –\(\frac{20}{10}\) = -2
Question 28.
The solution of the equation \(\frac { z }{ 2 } \) = \(\frac { 3 }{ 4 } \) is
(a) \(\frac { 1 }{ 2 } \)
(b) \(\frac { 3 }{ 2 } \)
(c) \(\frac { 1 }{ 4 } \)
(d) \(\frac { 3 }{ 4 } \)
Answer
Answer: (b) \(\frac { 3 }{ 2 } \)
Hint:
\(\frac{z}{2}\) = \(\frac{3}{4}\) ? z = \(\frac{3×2}{4}\) = \(\frac{3}{2}\)
Question 29.
The solution of the equation 2s = 0 is
(a) 2
(b) -2
(c) 0
(d) \(\frac { 1 }{ 2 } \)
Answer
Answer: (c) 0
Hint:
2s = 0 ? s = \(\frac{0}{2}\) = 0.
Question 30.
The solution of the equation – \(\frac { p }{ 7 } \) = 3 is
(a) -3
(b) -7
(c) -21
(d) 21
Answer
Answer: (c) -21
Hint:
–\(\frac{p}{7}\) = 3 ? -p = 3 × 7 = 21
? p = -21
Question 31.
The solution of the equation 4x + 5 = 9 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (a) 1
Hint:
4x + 5 = 9 ? 4x = 9 – 6 = 4
? x = \(\frac{4}{4}\) = 1.
Question 32.
The solution of the equation 10 y – 20 = 30 is
(a) 1
(b) 2
(c) 3
(d) 5
Answer
Answer: (d) 5
Hint:
10y – 20 = 30 ? 10y = 30 + 20 = 50
? y = \(\frac{50}{10}\) = 5.
Question 33.
The solution of the equation 3s + 6 = 0 is
(a) 1
(b) -1
(c) 2
(d) -2
Answer
Answer: (d) -2
Hint:
3s + 6 = 0
? 3s = -6 ? s = –\(\frac{6}{3}\) = -2.
Question 34.
The solution of the equation 10p = 10 is
(a) 1
(b) – 1
(c) 10
(d) – 10
Answer
Answer: (a) 1
Hint:
10p = 10 ? p = \(\frac{10}{10}\) = 1.
Question 35.
The solution of the equation 10p + 10 = 110 is
(a) 10
(b) -10
(c) 100
(d) 110
Answer
Answer: (a) 10
Hint:
10p + 10 = 110
? 10p = 110 – 10 = 100
? p = \(\frac{100}{10}\) = 10.
Question 36.
The solution of the equation – 4 = 2 (p – 2) is
(a) 0
(b) 1
(c) 2
(d) 4
Answer
Answer: (a) 0
Hint:
-4 = 2(p – 2) ? p – 2 = –\(\frac{4}{2}\) = -2
? p = -2 + 2 = 0.
Question 37.
The solution of the equation 0 = 4 + 4(m + 1) is
(a) 1
(b) -1
(c) 2
(d) -2
Answer
Answer: (d) -2
Hint:
0 = 4 + 4 (m + 1)
? 4(m + 1) = -4 ? m + 1 = –\(\frac{4}{4}\) = -1
m = -1 – 1 = -2.
Question 38.
The solution of the equation 12p – 11 = 13 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (b) 2
Hint:
12p – 11 = 13 ? 12p = 13 + 11 = 24
? p = \(\frac{24}{12}\) = 2.
Question 39.
The solution of the equation 2 (m + 3) = 8 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (a) 1
Hint:
2(m + 3) = 8 ? m + 3 = \(\frac{8}{2}\) = 4
? m = 4 – 3 = 1.
Question 40.
The solution of the equation – 2(x + 3) = 4 is
(a) -2
(b) -3
(c) -4
(d) -5
Answer
Answer: (d) -5
Hint:
-2 (x + 3) = 4 ? x + 3 = \(\frac{4}{-2}\) = -2
? x = -2 – 3 = -5.
Question 41.
The solution of the equation \(\frac { 5 }{ 2 } \) x = 15 is
(a) 2
(b) 4
(c) 6
(d) 10
Answer
Answer: (c) 6
Hint:
\(\frac{5}{2}\) x = 15 ? x = \(\frac{15×2}{5}\) = 6
Question 42.
The solution of the equation 4(2 – x) = 4 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (a) 1
Hint:
4 (2 – x) = 4 ? 2 – x = \(\frac{4}{4}\) = 1
? x = 2 – 1 = 1.
Question 43.
The solution of the equation -4(2 + x) = 4 is
(a) -1
(b) -2
(c) -3
(d) -4
Answer
Answer: (c) -3
Hint:
-4(2 + x) = 4 ? 2 + x = \(\frac{4}{-4}\) = -1
? x = -1 – 2 = -3.
Question 44.
The solution of the equation \(\frac { p }{ 2 } \) + 1 = 3 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (d) 4
Hint:
\(\frac{p}{2}\) + 1 = 3 ? \(\frac{p}{2}\) = 3 – 1 = 2
p = 2 × 2 = 4
Question 45.
The solution of the equation 3 m + 7=16 is
(a) 1
(b) 2
(c) 3
(d) 4
Answer
Answer: (c) 3
Hint:
3m + 7 = 16 ? 3m = 16 – 7 = 9
? m = \(\frac{9}{3}\) = 3
0 comments:
Post a Comment